ANALISIS KESULITAN GURU DAN SISWA DALAM BERADAPTASI DENGAN PERUBAHAN KURIKULUM DI INDONESIA - Rosda Maulida; Galuh Meita Putri; Fadinda Syifa Faozan; Sofyan Iskandar (Jurnal Lensa Pendas, 2025)
The Indonesian education system has undergone numerous curriculum modifications, commencing with the 1947 lesson plan curriculum and culminating in the implementation of the independent curriculum in 2022. These modifications were implemented with the objective of aligning educational practices with contemporary demands and the evolving needs of students in the modern era. This study employs the literature review method, which involves the analysis of various literatures and previous research relevant to the challenges experienced by teachers and students in adjusting to curriculum changes in Indonesia. By employing this method, the researcher was able to identify, analyze, and synthesize a series of related findings, in addition to describing the challenges faced by teachers and students in the dynamically changing curriculum. The extant research findings indicate that frequent curriculum changes can cause various problems for teachers and students. The challenges encountered by teachers can be attributed to a variety of factors, including the presence of unresolved conceptual issues, inadequate training and socialization, deficient facilities and infrastructure, the psychological impact on teachers, and the discrepancy between policies established and their implementation in the classroom. Concurrently, students are obligated to adapt to novel materials, divergent learning methodologies, and assessment systems that may appear alien to them.